Perceptions and Actions of Educational Policy Makers regarding Parental Engagement in Education - WAHYUDDIN WAHYUDDIN (Indonesian Research Journal in Education |IRJE|, 2018)
This study aimed to examine perceptions and actions of educational policy makers regarding parental engagement in children’s education within a district in West Sulawesi Province, Indonesia. The study employed a qualitative study using a phenomenological approach. Data were collected from five participants through a semi-structured interview, involving the head of the district, the education department head, a sub-district head, a village head, and a school principal. The collected data were analyzed by applying Moustakas’s (1994) analytical methods consisting of three steps namely bracketing, creating clusters of meaning, and textural description. The results showed that the policy makers within the district had an appropriate perception about the increment of parental involvement in education, not only for students but also for schools, parents, and local governments. However, positive perceptions of educational policy makers within the district were not consistent with their actions, proved by no particular policy intending for parental involvement.